Effects of an extracted lectin from Citrullus colocynthis L. (Cucurbitaceae) on survival, digestion and energy reserves of Ectomyelois ceratoniae Zeller (Lepidoptera: Pyralidae) - Ramzi, Samar (Frontiers in Physiology, 2013)
Lectins are the widespread and heterogeneous proteins of plants that serve as storage proteins in defensive mechanisms against herbivores. A lectin was extracted and purified from seeds of Citrullus colocynthis by Sepharose 4B-Galactose and DEAE-cellulose fast flow chromatographies. Different concentrations of the lectin were added to artificial diet of Ectomyelois ceratoniae to find out its effect on some biological parameters, digestive physiology and amount of storage macromolecules. It was found that CCA increased life span from 23.44 days in control to 28.59 days in the individuals fed on 2% of CCA. Larval survivals on control and CCA diets were 93.3 and 66.6%, respectively. Different concentrations of CCA significantly affected α-amylase and general proteolytic activities in larvae but TAG-lipase activity had no significant changes. Activities of all specific proteases decreased when larvae were fed on different concentrations of CCA except for aminopeptidase. Meanwhile, amount of storage macromolecules in the larvae fed on different concentrations of CCA statistically decreased versus control. These results demonstrated that CCA could intervene in physiology of E. ceratoniae and survival of larvae. Therefore, it can be taken into consideration in IPM of the pest through plant breeding programs.